Collectins and ficolins in neonatal health and disease - Cedzyński, Maciej; Świerzko, Anna S. (Frontiers in Immunology, 2023)
The immune system starts to develop early in embryogenesis. However, at birth it is still immature and associated with high susceptibility to infection. Adaptation to extrauterine conditions requires a balance between colonization with normal flora and protection from pathogens. Infections, oxidative stress and invasive therapeutic procedures may lead to transient organ dysfunction or permanent damage and perhaps even death. Newborns are primarily protected by innate immune mechanisms. Collectins (mannose-binding lectin, collectin-10, collectin-11, collectin-12, surfactant protein A, surfactant protein D) and ficolins (ficolin-1, ficolin-2, ficolin-3) are oligomeric, collagen-related defence lectins, involved in innate immune response. In this review, we discuss the structure, specificity, genetics and role of collectins and ficolins in neonatal health and disease. Their clinical associations (protective or pathogenic influence) depend on a variety of variables, including genetic polymorphisms, gestational age, method of delivery, and maternal/environmental microflora.